Israel : Report on the Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2005)
This report assesses Observance of Standards and Codes on Financial Action Task Force (FATF) Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) for Israel. Israel has made significant progress in strengthening its regime for AML/CFT since 2000. Overall, a comprehensive legal and institutional framework for AML/CFT is now in place, and Israel complies well with the FATF 40+8 Recommendations. The assessment, nevertheless, identified a number of areas where the regime for AML/CFT could be strengthened, including the need to ensure more consistency among the relevant supervisory authorities in addressing AML/CFT problems.